2000
DOI: 10.1111/j.1528-1157.2000.tb00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Myoclonus Associated with the Use of Gabapentin

Abstract: Summary:Purpose: To report on the occurrence of myoclonus in patients receiving gabapentin (GBP) for the treatment of epilepsy.Methods: Clinic charts of 104 consecutive patients started on GBP were reviewed. All patients were treated by the same physician, and most were specifically asked about the presence of myoclonus.Results: We found 13 cases of myoclonus. All patients had refractory epilepsy and were taking other antiepileptic drugs (AEDs). Six patients had a severe chronic static encephalopathy; five pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 6 publications
0
56
0
1
Order By: Relevance
“…Seizure aggravation as a consequence of prescribing an inappropriate AED for the particular seizure type or because of a paradoxical exacerbation of seizures should be followed by prompt review of treatment [8][9][10][11][12][13][14][15][16][17][18] (table II). Once identified, the most appropriate AED, starting with low doses, slow titration, adequate posology choice and individualization of the minimal effective maintenance doses, may greatly improve safety and tolerability.…”
Section: Safety and Tolerability: General Considerationsmentioning
confidence: 99%
“…Seizure aggravation as a consequence of prescribing an inappropriate AED for the particular seizure type or because of a paradoxical exacerbation of seizures should be followed by prompt review of treatment [8][9][10][11][12][13][14][15][16][17][18] (table II). Once identified, the most appropriate AED, starting with low doses, slow titration, adequate posology choice and individualization of the minimal effective maintenance doses, may greatly improve safety and tolerability.…”
Section: Safety and Tolerability: General Considerationsmentioning
confidence: 99%
“…One case series and one case report identified worsening of myoclonic seizures in this population when they were treated with gabapentin. 9,10,76 Lamotrigine. One study with class I 77 and one with class II evidence 78 were identified.…”
Section: Treatment Of Refractory Epilepsy In Children Question 4: Whmentioning
confidence: 99%
“…5 This adverse event was reported as well in open trials. Review of adverse events in open trials and case reports revealed involuntary move- ments presenting as myoclonus, 9 choreoathetosis, [10][11][12] and incontinence of bowel and bladder. 13 No significant changes in serum levels of concomitant AEDs were identified in these studies, demonstrating the lack of interaction between gabapentin and other AEDs.…”
mentioning
confidence: 99%
“…36 All had refractory epilepsy and six had an epileptic encephalopathy. The myoclonus was mild and may have been non-epileptic.…”
Section: Gbpmentioning
confidence: 99%